Competency, Compensation, and Workload Occupational Therapist Performance with Motivation as a Moderating - Hastuti, Sri; DPW, Ida Aryati; Pawenang, Supawi (Indonesian Journal of Islamic Economics and Finance, 2023)
This study aims to test and analyze the effect of competence, compensation, and workload on the performance of Occupational Therapists in the Sukoharjo area with motivation as a moderation variable. Data collection technique is a method of collecting data obtained directly to the research location This research is a descriptive quantitative research with a population and sample of 40 (forty) people. The research instruments are questionnaires with Likert scales and analysis using the Partial Least Square method and alternative methods of analysis with variance-based Structural Equation Modeling (SEM). Based on the results of research on the effect of competence, compensation, and workload on the performance of Occupational Therapists in Sukoharjo area institutions with motivation as a moderating variable, it can be concluded that Competence has a positive and significant effect directly on the performance of Occupational Therapists working in Sukoharjo regional institutions, Compensation, Motivation and Work Expenses do not have a positive and significant effect directly on the performance of Occupational Therapists working in Sukoharjo regional institutions. Motivation is not able to moderate the effect of Competency on the Occupational Performance of Therapists Working in Sukoharjo area institutions. Motivation is unable to moderate the effect of compensation on the occupational performance of therapists working in institutions in the Sukoharjo area. Motivation is unable to moderate the effect of workload on the Occupational Performance of Therapists Working in Sukoharjo area institutions